A state-of-the-art review on high temperature resistance of lightweight aggregate high-strength concrete. (15th June 2023) - Bao, Jiuwen; Zheng, Rui; Sun, Yanqun; Zhang, Peng; Cui, Yifei; Xue, Shanbin; Song, Qiang
Abstract: Lightweight aggregate high-strength concrete (LWA-HSC) exposed to high temperatures usually exhibits the poor resistance to the deterioration properties of materials, which would be bring about a serious threat to the safety of concrete structures after fire disaster or high temperature action. It is of great significance to explore the damage mechanism of LWA-HSC at elevated temperatures aiming at its popularization and application in the practical engineering. Based on the research status of LWA-HSC performance behavior at home and abroad, the damage evolution mechanisms of concrete at elevated temperatures were first summarized and introduced. The influence of some factors, including lightweight aggregate types and dosage, replacement ratio, heating rate, and cooling system, on the mechanical and durability-related properties of LWA-HSC after high temperatures was further discussed, and the strengthening mechanisms of the resistance to high temperature was elaborated and analyzed. On this basis, the future research on the performance behavior of LWA-HSC would be finally proposed, which is helpful to perfect theoretical development and technological innovation. Highlights: Damage mechanisms of concrete exposed to high temperatures were summarized. Mechanical and durability-related properties of LWA-SHC after high temperature were reviewed. Modeling of high temperature damage behavior of LWA-HSC were discussed. Some performance enhancement methods of damaged LWA-HSC were analyzed. Future research on the performance behavior of LWA-HSC would be proposed.